Clinical presentation of women with fibroid uterus admitted for surgical management at a tertiary care teaching hospital - Duwal Shrestha, Sarada; Maharjan, Anjali; Timalsina, Gyanu (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Uterine fibroids are common benign tumors causing menstrual disturbances, pelvic pain, and infertility. Although many women require surgical management, data on their clinical presentation and treatment patterns in Nepal are limited. This study aimed to assess the clinical presentation, fibroid characteristics, and surgical management of women admitted with fibroid uterus at a tertiary care teaching hospital. Method: This retrospective observational study was conducted in the Department of Obstetrics and Gynaecology, Patan Hospital, Patan Academy of Health Sciences, from Jul 2022 to Jun 2025, after ethical approval. All surgically managed cases of fibroid uterus were included, and data on demographics, clinical presentation, fibroid characteristics, and surgical procedures were analyzed using descriptive statistics. Result: A total of 218 patients were included, most were aged 41–50 years (59.63%) and multiparous (71.56%). Menorrhagia (37.61%) was the most common symptom, followed by lower abdominal pain (25.69%) and mixed complaints (20.64%). Intramural fibroids were predominant (61.47%), with single fibroids in 55.05% of cases. Fibroid sizes were commonly 12–14 weeks (18.35%) and 16–18 weeks (17.89%). Total abdominal hysterectomy with bilateral salpingo-oophorectomy was the main surgical procedure (65.14%), followed by myomectomy (10.55%). Conclusion: Uterine fibroids were most common in women aged 41–50 years, with menorrhagia as the main symptom. Intramural fibroids of 12–18 weeks were most common, with hysterectomy as the primary treatment and myomectomy selectively performed for fertility preservation, emphasizing the need for timely evaluation and individualized management.